Soluble and insoluble dietary fiber at different ratios: Hydration characteristics, rheological properties, and ameliorative effects on constipation - Lijuan Wang; Jiaxin Wang; Jialin Wang; Zicong Guo; Zaigui Li; Ju Qiu; Lili Wang (Food Chemistry: X)
The proportion of soluble components in dietary fiber is an important factor affecting its physicochemical properties and physiological functions. The influence mechanisms of insoluble (IDF) and soluble dietary fiber (SDF) at different ratios on constipation were investigated. Results showed that SDF had higher active groups and water swelling capacity than IDF. The viscosity of chyme with SDF alone was the highest in oral and gastric phases. The gastric emptying rate and small intestine propulsion capacity increased significantly, especially when IDF/SDF was 1:1. IDF and a lower proportion of SDF (< 50 %) promoted gut microbiota diversity and short-chain fatty acids production. The contents of 5-hydroxytryptamine, acetylcholinesterase and gastrin reached the maximum value when the IDF ratio was 50 %. In conclusion, IDF could act synergistically with SDF to promote defecation and relieve constipation, and the effect was the best when the ratio of IDF to SDF was 1:1.